The demographic and clinical profile of HIV infected and non- infected children and adolescents attending two district psychiatric clinics in Sedibeng: a retrospective record review - Makofane, Lerato (University of the Witwatersrand, Johannesburg, 2024)
Background: A limited district-based child and adolescent psychiatric service is provided in Gauteng province. Mental disorders are common in children and adolescents living with HIV and there is a bidirectional relationship between mental health and HIV. Aim: To ascertain the prevalence of HIV among children and adolescents attending two clinics and to compare clinical correlates of those living with and without HIV. Setting: Child and adolescent psychiatric clinics based at two community health centres (Zone 12 Clinic in Sebokeng township and Johan Heyns Clinic in a suburban area of Vanderbijl Park) in the Sedibeng district of Gauteng province. Methods: A retrospective record review was conducted of all active files. Results: 370 records (232 from Johan Heyns and 138 from Zone 12) were retrieved. Only five (1.4%) users were living with HIV, therefore no comparison could be made between users with and without HIV. All five users living with HIV were male and Black African, with an age range of 9-22 years. Of the five, three had one deceased parent and two had lost both parents. Psychiatric diagnoses were intellectual disability (n=3), epilepsy (n=3), ADHD (n=3), depression (n=1), and traumatic brain injury (n=1). Conclusion: Very few children and adolescents living with HIV attended either clinic. The sample reflects different help-seeking priorities and access among different communities regarding mental health. More services and research focusing on community child and adolescent mental health services is required.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Medicine in the branch of Psychiatry in a submissive format to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, Johannesburg, 2024
Keywords: HIV; Children and adscolents; Mental health; District mental health; UCTD; SDG-3: Good health and well-being